Da Idade Média para o Renascimento: o caso de Doctor Faustus de Christopher Marlowe - Neckel Junior, Fernando Azevedo (2016)
Marlowe certainly composed a play with a high structural ambiguity, thus this work investigates the elements of the play Doctor Faustus that refer to the dramatic tradition of the Middle Ages, specifically the English moralities, and the very elements of Renaissance theater. To this end, we used primarily a description of the source, the Faustbook, and the context in which the play is placed. One of the central issues in the study of this play concerns the two versions that survived, both published after the author’s death, the first in 1604 and second in 1616, they are commonly called the A-text and the B-text, respectively. We aim to make a comparison between the play and its source text, taking into account structural and thematic aspects that emphasize the nature of the sin committed by Faust. After the comparative study, and given the protagonist's ambiguity, this study aims to select and analyze fragments that suggest the two interpretations, as a morality or as a Renaissance tragedy. Then, we consider the reasons Fausto makes his covenant: necromancy. Finally, there is a curious aspect in the play that also deals with its structural ambiguity: its comic scenes. The burlesque in the play presents a kind of fusion between hero and clown, what makes Faust a more complex character than a traditional tragic hero.